Hmong in Vietnam : a tradition in flux. - Wong, Gillian Jin-Lin. (2008)
This projects is about understanding how the country’s turbulent history has shaped Vietnam that it is today. The author of this project wanted to observe the meeting of Vietnam’s communist politics and “socialist-oriented market economics” from the inside. And also, to see the cultural and social changes brought by rapid industrialisation and foreign investment in one of Southeast Asia’s poorest countries.